(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
"Green economy" as an economic system is still a very controversial topic. This article highlights the origin, goals, and objectives of the "green economy" and its differences from the traditional economy. The efforts of the world’s societies related to long-term sustainable development and better living will be strengthened in the context of the "green economy". This article presents the main drivers of the "green economy". At the same time, the results achieved in the implementation of the green economy in Uzbekistan are analyzed.